PENGARUH HIPNOTERAPI TERHADAP IBU PRALANSIA DENGAN HIPERTENSI DI KELURAHAN SETIAMULYA KOTA TASIKMALAYA - Dita Eka Mardiani; Debby Inda Rabbi; Nunung Mulyana (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2020)
have not been able to restrain or control hypertension blood pressure and require a combinationintervention of pharmacological drugs andnon-pharmacological medication. The purpose of this researchis to find out the influence of hypnotherapy on blood pressure in pre-elderly mothers with hypertension.Methodology. The research is aquasi-experimental research with One-group pre-post-test design. Thepopulation includes 62 pre-elderly mothers with hypertension, and 30 samples were chosen usingPurposive Sampling. The variables are hypnotherapy and blood pressure. This research uses bloodpressure meter and stethoscope as instruments. Wilcoxon test is used to analyze the data. Discussion ofthis study is before hypnotherapy was conducted, most of the systole is 140 and the diastole is 90. Whereas, after the hypnotherapy is done, almost all respondents have undergone changes, with most of thesystole is 120 and the diastole is 80. Wilcoxon test results significance (p value) 0.000 0.05. Conclusionof this research is that there is an influence of hypnotherapy on blood pressure in pre-elderly mothers withhypertension in Kelurahan Setiamulya under the work territory of Puskesmas Tamansari Kota Tasikmalaya.When the respondents are given hypnotherapy, endorphin is released which makes the body feels comfortand happy, life quality can increase and blood pressure can be controlled.